Improving the Stability of Ink-Jet Printed Red Qleds by Optimizing the Device Fabrication Process - Özçelik, Serdar; Diker, H.; Varlıklı, Canan; Unluturk, S.S.; Ozcelik, S.; Varlikli, C. (Eurasia Academic Publishing Group, 2024)
Red-light emitting Cadmium Sulfide0.8 Selenide0.2 / Zinc Sulfide (CdS0.8 Se0.2 /ZnS) based quantum dots (QDs) were synthesized by hot injection method and utilized as the emissive layer in the quantum dot light emitting diode (QLED) with the device structure of Indium Tin Oxide/Poly(3,4-ethylenedioxythiophene): Polystyrene Sulfonate /Polyvinylcarbazole(or Poly (N,N'-bis-4-butylphenyl-N,N'-bisphenyl)benzidin)/QD/ZincOxide/ LithiumFluoride/ Aluminum [ITO/ PEDOT: PSS/PVK(or p-TPD)/ QD/ZnO/LiF/Al]. QD inks were formulated and prepared in octane: decane; (1/1, v/v) solvent system and mixed with the nonionic surfactant, TritonX-100, to make the QD inks inkjet printable. In addition to the inkjet printing technique, spin coating was also employed to form the QD emissive layer for comparing device performance. Compared to the p-TPD-based QLED device, the PVK-based device fabricated via spin coating exhibited ~6-fold higher performance in terms of luminance and efficiency values. In the case of using the ink-jet printer, ~2-fold higher maximum luminance value and slightly lower external quantum efficiency at the lower current density region were obtained in the p-TPD-based device. Furthermore, compared to the PVK layer, the p-TPD layer provided higher device stability regardless of the coating method at the higher current density regions. We suggest that the coating method applied and the choice of hole transport layer (HTL) materials may control the device parameters. © The Author(s), 2024.
Keywords: Hole Transport Material; Inkjet Printing; Qd Ink Formulation; Quantum Dots; Red Quantum Dot Light Emitting Diode (QLED)